new aquareovirus causing high mortality in farmed Atlantic halibut fry in Norway - Blindheim, Steffen; Nylund, Are; Watanabe, Kuninori; Plarre, Heidrun; Erstad, Børre; Nylund, Stian (Archives of virology, 2015)
A new aquareovirus was isolated from cultured Atlantic halibut (Hippoglossus hippoglossus) fry at a facility where massive mortalities had occurred during the start-feeding phase. The same virus was also detected in juveniles (about 10 grams) of the 2013 generation at two other production sites, but not in larger fish from generations 2007–2012. The virus replicated in BF-2 and CHSE-214 cell cultures and produced syncytia and plaque-like cytopathic effects. This Atlantic halibut reovirus (AHRV) was associated with necrosis of the liver and pancreas, syncytium formation in these tissues, and distinct viroplasm areas within the syncytium in halibut fry. Transmission electron microscopy revealed that the viroplasm contained virions, non-enveloped, icosahedral particles approximately 70 nm in diameter with a double capsid layer, amorphous material, and tubular structures. The RNA-dependent RNA polymerase (RdRp) gene from the AHRV isolates showed the highest amino acid sequence identity (80 %) to an isolate belonging to the species Aquareovirus A, Atlantic salmon reovirus TS (ASRV-TS). A partial sequence from the putative fusion-associated small transmembrane (FAST) protein of AHRV was obtained, and this sequence showed the highest amino acid sequence identity (46.8 %) to Green River Chinook virus which is an unassigned member of the genus Aquareovirus, while a comparison with isolates belonging to the species Aquareovirus A showed <33 % identity. A proper assessment of the relationship of AHRV to all members of the genus Aquareovirus, however, is hampered by the absence of genetic data from members of several Aquareovirus species. AHRV is the first aquareovirus isolated from a marine coldwater fish species and the second reovirus detected in farmed fish in Norway. A similar disease of halibut fry, as described in this paper, has also been described in halibut production facilities in Canada and Scotland.